KAJIAN ASPEK PSIKOLOGI TOKOH UTAMA DALAM NOVEL LAYLA-MAJNUN KARYA SHOLEH GISYMAR - Risa Delva Yendri; Bakhtaruddin Nasution; Muhammad Ismail Nasution (Faculty of Languages and Arts, Universitas Negeri Padang, 2013)
This article describes: (1) Layla-Majnun novel structure Sholeh Gisyamar work, (2) the main character in the novel psychological Layla-Majnun works Sholeh Gisyamar of aspects of id, ego, superego. This data was collected by way of reading the novel Layla-Majnun Gisymar Sholeh work, marking the language related to the research problem. The findings of the research, a novel structure-Majnun Layla Gisymar Sholeh work consisting of plot, setting, characterization, theme and the message, style, and point of view. While the discussion of the psychological aspects of the figure consists of the id, ego, and superego. Based on the results of this study concluded that, aspects of the main character's personality is more likely to attach great importance to the principle of the id ego gratification. Aspects of the ego is not balanced with the character superego aspect, then in the event of self-awareness on the figure, the ego back into play so that the resulting chaos and abnormal action. So the role of the superego in Layla-Majnun novel works Sholeh Gisymar only slightly.